Sufficient Numbers of Early Germ Cells Are Essential for Female Sex Development in Zebrafish - Dai, Xiangyan (PLoS One, 2015)
The sex determination for zebrafish is controlled by a combination of genetic and environmental factors. The determination of sex in zebrafish has been suggested to rely on a mechanism that is affected by germ cell-derived signals. To begin our current study, a simplified and efficient germ cell-specific promoter of the dead end (dnd) gene was identified. Utilizing the metrodinazole (MTZ)/ bacterial nitroreductase (NTR) system for inducible germ cell ablation, several stable Tg (dnd:NTR-EGFP(-3'UTR)) and Tg (dnd:NTR-EGFP(+3'UTR)) zebrafish lines were then generated with the identified promoter. A thorough comparison of the expression patterns and tissue distributions of endogenous dnd and ntr-egfp transcripts in vivo revealed that the identified 2032-bp zebrafish dnd promoter can recapitulate dnd expression faithfully in stable transgenic zebrafish. The correlation between the levels of the germ cell-derived signals and requirement for maintaining the female fate has been also explored with different durations of the MTZ treatments. Our results revealed the decreasing ratios of female presented in the treated transgenic group are fairly associated with the reducing levels of the early germ cell-derived signals. After the juvenile transgenic fish treated with 5 mM MTZ for 20 days, all MTZ-treated transgenic fish exclusively developed into males with subfertilities. Taken together, our results identified here a simplified and efficient dnd promoter, and provide clear evidence indicating that it was not the presence but the sufficiency of signals derived from germ cells that is essential for female sex development in zebrafish. Our model also provides a unique system for sex control in zebrafish studies.